2015
DOI: 10.1097/aog.0000000000000592
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Endometriosis on Assisted Reproductive Technology Outcomes

Abstract: Women with and without endometriosis have comparable ART outcomes in terms of live births, whereas those with severe endometriosis have inferior outcomes. There is insufficient evidence to recommend surgery routinely before undergoing ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 69 publications
7
84
1
5
Order By: Relevance
“…A recent two meta-analysis have focused on the OS characteristics and ART outcomes of women with intact endometriomas (6,24). According to Hamdan et al, women with intact endometrioma revealed lower number of retrieved oocytes when compared to women with no endometriosis (SMD -0.23; 95% CI (-0.37, -0.10) (6). Similarly, pooled data from the meta-analysis of Yang et al revealed 1.50 fewer oocytes retrieved in women with ovarian endometrioma than in those without endometrioma (WMD -1.50; 95% CI -2.84 to -0.15, P=0.03) (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent two meta-analysis have focused on the OS characteristics and ART outcomes of women with intact endometriomas (6,24). According to Hamdan et al, women with intact endometrioma revealed lower number of retrieved oocytes when compared to women with no endometriosis (SMD -0.23; 95% CI (-0.37, -0.10) (6). Similarly, pooled data from the meta-analysis of Yang et al revealed 1.50 fewer oocytes retrieved in women with ovarian endometrioma than in those without endometrioma (WMD -1.50; 95% CI -2.84 to -0.15, P=0.03) (24).…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, endometrioma cases were compared to that of other infertility etiologies including male or tubal factor infertility (8,(21)(22)(23). A recent two meta-analysis have focused on the OS characteristics and ART outcomes of women with intact endometriomas (6,24). According to Hamdan et al, women with intact endometrioma revealed lower number of retrieved oocytes when compared to women with no endometriosis (SMD -0.23; 95% CI (-0.37, -0.10) (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, it is also present in 20-40% of women undergoing IVF and is often associated with lower rates of live births, clinical pregnancy and implantation rates [3][4][5]. Women with Stage III and IV endometriosis can develop endometriomas, or cysts arising from ectopic endometrial tissue implanted in the ovary with invagination of the ovarian cortex.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of IVF, endometriomas can make oocyte aspiration difficult due to limited visualization of the follicular cohort [6,7]. As a result, clinicians often obtain a lower yield of oocytes [4]. In addition, there is an increased risk of inadvertent fenestration of the endometrioma, which has been shown to cause inflammatory peritonitis, and if aspirated into the egg retrieval needle, can be detrimental to the oocyte [8].…”
Section: Introductionmentioning
confidence: 99%